THE INFLUENCE OF ORGANIZATIONAL CULTURE, PROFESSIONAL ETHICS AND AUDITOR COMPETENCE ON EMPLOYEE PERFORMANCE AT THE REPRESENTATIVE FINANCIAL AUDIT BOARD OF CENTRAL KALIMANTAN - Dewi Maharani, Rochima (Gapenas Publisher, 2024)
This research aims to analyze the influence of organizational culture, professional ethics and auditor competence on employee performance at the Representative Financial Audit Agency of Central Kalimantan Province. This research was conducted at the Central Kalimantan Representative Financial Audit Agency. The research method used in this research is a quantitative approach, research instruments through the distribution of questionnaires distributed to 92 auditor respondents. This research uses SEM PLS with the smartPLS 3.0 research instrument The results of data analysis and hypothesis testing show that organizational culture has no significant effect on the performance of employees of the Representative Audit Agency of Central Kalimantan Province, professional ethics has a significant effect on the performance of employees of the Representative Audit Agency of Central Kalimantan Province and auditor competency has a significant effect on the performance of employees of the Representative Audit Agency of Finance. Central Kalimantan Province